2022
DOI: 10.1111/ppl.13834
|View full text |Cite
|
Sign up to set email alerts
|

The PavNAC56 transcription factor positively regulates fruit ripening and softening in sweet cherry (Prunus avium)

Abstract: The rapid softening of sweet cherry fruits during ripening results in the deterioration of fruit quality. However, few genes related to sweet cherry fruit ripening and softening have been identified, and the molecular regulatory mechanisms underlying this process are poorly understood. Here, we identified and functionally characterized PavNAC56, a NAC transcription factor that positively regulates sweet cherry fruit ripening and softening. Gene expression analyses showed that PavNAC56 was specifically and abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Because the NAC family exists from aquatic green algae to higher terrestrial plants, its members participate in the formation of the organ boundaries of plants transiting from vegetative growth to reproductive growth and are related to flower development and fruit ripening, which are essential to crop yield and quality (Maugarny-Calès et al, 2016;Ma et al, 2017;Mathew and Agarwal, 2018;Forlani et al, 2021;Singh et al, 2021;Liu G. S. et al, 2022). Thereby, in recent years, much progress has been made toward understanding the molecular mechanisms regulated by NAC TFs in flower development (Guo et al, 2022;Liang et al, 2022;Liu X. et al, 2022;Wang et al, 2022;Ghissing et al, 2023) and fruit ripening (Fu B. L. et al, 2021;Gao et al, 2021;Kou et al, 2021;Gao et al, 2022;Liu B. et al, 2022;Qi et al, 2022). In this review, we mainly summarize up-to-date advances on the basic properties, function, and action mechanisms of NACs in flower formation, flowering, and fruit ripening to improve our understanding of the molecular basis of crop yield and quality mediated by NAC TFs.…”
Section: Introductionmentioning
confidence: 99%
“…Because the NAC family exists from aquatic green algae to higher terrestrial plants, its members participate in the formation of the organ boundaries of plants transiting from vegetative growth to reproductive growth and are related to flower development and fruit ripening, which are essential to crop yield and quality (Maugarny-Calès et al, 2016;Ma et al, 2017;Mathew and Agarwal, 2018;Forlani et al, 2021;Singh et al, 2021;Liu G. S. et al, 2022). Thereby, in recent years, much progress has been made toward understanding the molecular mechanisms regulated by NAC TFs in flower development (Guo et al, 2022;Liang et al, 2022;Liu X. et al, 2022;Wang et al, 2022;Ghissing et al, 2023) and fruit ripening (Fu B. L. et al, 2021;Gao et al, 2021;Kou et al, 2021;Gao et al, 2022;Liu B. et al, 2022;Qi et al, 2022). In this review, we mainly summarize up-to-date advances on the basic properties, function, and action mechanisms of NACs in flower formation, flowering, and fruit ripening to improve our understanding of the molecular basis of crop yield and quality mediated by NAC TFs.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit ripening and softening is a coordinated complex developmental and process, particularly in climacteric fruits, such as those of Prunus species, which have a short ripening period and a fast softening period (García‐Gómez et al ., 2020, 2021). Numerous studies on fruit firmness or softening have focused on the roles of cell wall‐modifying enzymes (Atkinson et al ., 2012; García‐Gómez et al ., 2020, 2021; Phan et al ., 2007; Shi et al ., 2022; Zhang et al ., 2022); softening‐related transcription factors, such as members of the MADS‐box and NAC (NAM, ATAF and CUC) families, which directly regulate cell‐wall‐modifying genes (Fujisawa et al ., 2011; Gao et al ., 2020; García‐Gómez et al ., 2021; Qi et al ., 2022; Shi et al ., 2022); and ethylene/abscisic acid biosynthetic genes (Jia et al ., 2011; Shi et al ., 2022; Seymour, Poole, et al ., 2013). Interestingly, in the present study, a serine carboxypeptidase‐like protein, PavSCPL, was shown to play a vital function in controlling fruit firmness by BSA‐seq and fine‐mapping analysis, and this is the first report of a SCPL‐encoding candidate gene involved in the control of fruit firmness among perennial Rosaceae crops.…”
Section: Discussionmentioning
confidence: 99%
“…An approximately 300‐bp coding region fragment of PavSCPL was cloned into the pTRV2 vector to generate pTRV2‐PavSCPL, which was transformed into A. tumefaciens strain GV3101. The TRV‐mediated silencing of PavSCPL in sweet cherry fruit was implemented as described previously (Li et al ., 2015; Qi et al ., 2017, 2022) with the following modifications. (i) Agrobacterium tumefaciens strain GV3101 was cultured overnight at 28 °C to an OD 600 of 0.7–0.8 and then resuspended in A. tumefaciens infiltration buffer (10 m m MgCl 2 , 10 m m MES at pH 5.6 and 100 μ m acetosyringone) to a final OD 600 of 0.8–1.0.…”
Section: Methodsmentioning
confidence: 99%
“…Under the influence of ABA-induced transcription factor PavDof6, the expression of genes associated with cell wall degradation, named PavPME44 , PavPL18 , PavXTH31 , and PavXTH26 , are up-regulated, however, the inhibition of PavDof2/15 by ABA decreases the expression of these genes ( Zhai et al., 2022 ). Analogously, ABA-induced PavNAC56 directly activate the expression of cell wall-related genes PavPG2 , PavEXPA4 , PavPL18 and PavCEL8 ( Qi et al., 2022 ). Ethylene biosynthesis genes SlACS2/4 , color-related genes SlGgpps2 and SlSGR1 , and cell-wall-related genes SlPG2a , SlPL , SlCEL2 and SlEXP1 , are all direct targets of ABA-induced NAC TF NOR-like1 ( Gao et al., 2018 ).…”
Section: Aba Signaling During Fruit Ripeningmentioning
confidence: 99%